Clinical Outcome of 1064-nm Picosecond Neodymium–Doped Yttrium Aluminium Garnet Laser for the Treatment of Hypertrophic Scars. (17th February 2019) - Choi, Young-Jun; Kim, Jung Yup; Nam, Jae-Hui; Lee, Ga-Young; Kim, Won-Serk
ABSTRACT: Background: Currently no study has evaluated the effect of the novel 1064–nm picosecond neodymium-doped:yttrium aluminium garnet laser (ps–Nd:YAG) for reducing Hypertrophic scarring (HS).Objective: The aim of this study was to verify the efficacy and safety of a 1064-nm ps-Nd:YAG in the management of HS.Materials and Methods: A retrospective chart review and photographic analysis were conducted on patients treated with a low-fluence 1064-nm ps-Nd:YAG for HS improvement. The Vancouver Scar Scale (VSS), 5-point Global Assessment Score (GAS), and patient satisfaction score were used to determine the effect of scar improvement.Results: A total of 24 Korean patients (9 males and 15 females; mean age of 33.25 ± 15.50 years) were retrospectively evaluated. Mean treatment settings were 1064-nm wavelength, 750 ps pulse duration, 7.94 mm spot size, 0.93 J/cm 2 fluence, and 9.69 Hz frequency. The average VSS score decreased significantly (from 5.33 to 2.71) after laser treatment ( p < 0.001). The average GAS (3.02 ± 0.93) showed fair cosmetic improvement, and patient satisfaction scores (6.88 ± 2.66) indicated moderate satisfaction.Conclusion: The novel low-fluence 1064-nm ps-Nd:YAG could be considered as an effective and safe optional modality for the treatment of HS in Asian skin.